The goal and objectives of role play. (Texas Journal of Multidisciplinary Studies, 2025)
The purpose of role play is to help trainees foster their language and communicative skills as they stimulate trainees’ interaction in meaningful and early realistic situations. There are different types of role plays ranging from a mini-dialogue to a “scientific conference”. (T.I. Ignatova ). Actually the objective of this abstract is to share the experience how a role play “Making the Presentation” can be effectively used as a useful activity in training translators and interpreters. The “Translation Course” curriculum includes “General English”, ‘Specialist (Business) English”, “Translation Theory and Practice”, “The Language of Meetings”. These subjects are aimed at developing four language and especially oral skills. It is really challenging since our trainees have neither English speaking environment, nor many overseas people to communicate. The emergence of foreign firms and joint ventures as well as some foreign English experts are the factors that motivate our trainees to learn as foreign language and develop communicative skills. To help them effectively do it, I have been searching for the adequate activity. My four years’ practice of teaching prompted the role play “Making the Presentation”